Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/10934520802171675
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent toxicity of silica nano-particles toChlorella kessleri

Abstract: SiO(2) nano-particles were found to exhibit size-dependent toxicity toward the alga, Chlorella kessleri. Small SiO(2) nano-particles exhibit stronger toxicity: 50% inhibitory concentrations (IC(50)) value for 5 nm = 0.8 +/- 0.6%, 26 nm = 7.1 +/- 2.8%, and 78 nm = 9.1 +/- 4.7%. Enlargement of the cell body was observed by flow cytometry, which is due to the presence of structures that obstructed cell division. Optical and transmission microscopes were used to observe coagulated cells with incomplete division. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…In addition, the stability of released SiO 2 ENPs in solution strongly depends on pH, ionic strength and the natural silicon dioxide concentration in the environment (Michel et al, 2013). Research on the fate and effects of SiO 2 ENPs has been completed almost exclusively on pristine material, such as for example with algae (Fujiwara et al, 2008), Daphnia and aquatic midges (Lee et al, 2009), rather than focusing on the released silica. The fate of SiO 2 ENPs has been studied in wastewater and soil compartments (Chang et al, 2007;Jarvie et al, 2009;Lecoanet et al, 2004;Wiesner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the stability of released SiO 2 ENPs in solution strongly depends on pH, ionic strength and the natural silicon dioxide concentration in the environment (Michel et al, 2013). Research on the fate and effects of SiO 2 ENPs has been completed almost exclusively on pristine material, such as for example with algae (Fujiwara et al, 2008), Daphnia and aquatic midges (Lee et al, 2009), rather than focusing on the released silica. The fate of SiO 2 ENPs has been studied in wastewater and soil compartments (Chang et al, 2007;Jarvie et al, 2009;Lecoanet et al, 2004;Wiesner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alga is one of normally used model organism for the toxicity examination of toxicants and nanoparticles as well. Nanoparticulate CuO [10], ZnO [11], TiO 2 [12], Ag [13], CeO 2 [14], and SiO 2 [15,16] were all observed able to inhibit the growth of varieties of algae. Explanations of the toxicity mechanism varied with nanoparticle variety and in different studies.…”
Section: Introductionmentioning
confidence: 96%
“…TiO 2 and SiO 2 NPs were observed to be able to inhibit the growth of varieties of algae (Fujiwara et al 2008;Hall et al 2009;Van Hoecke et al 2008). Van Hoecke et al (2008) showed that different sizes of SiO 2 were toxic to Pseudokirchneriella subcapitata, with an EC20 for the growth rate in the range of 20.0-28.8 mg L −1 ; Ji et al (2011), in a study about the green algae Chlorella, reported that SiO 2 had no significant toxicity while TiO 2 NPs (HR3, anatase) greatly inhibited the algal growth with an EC30 of 30 mg L −1 .…”
Section: Introductionmentioning
confidence: 98%